Evaluasi Sistem Administrasi Pengajuan Hibah dalam Mendukung Pengembangan Sistem Berbasis Online pada Biro Kesejahteraan Rakyat Sekretariat Daerah Kalimantan Tengah - Zahra Widya Putri; Vivy Kristinae; Selly Aulia Margareta; Fricella Aprianda (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the administrative process of grant applications and evaluate the effectiveness of the system implemented at the Public Welfare Bureau of the Regional Secretariat of Central Kalimantan. The study employs a qualitative approach with a descriptive method, using interviews, observations, and documentation as data collection techniques. The results indicate that the grant application process has been carried out in accordance with established procedures; however, it is still dominated by a manual system that is less efficient in handling a high volume of applications. Although an online-based grant application system has been developed, its implementation has not been optimal due to the lack of full integration, limited socialization, and users’ readiness constraints.This study emphasizes the importance of developing a more integrated and adaptive online system to improve effectiveness, efficiency, and transparency in regional grant management.